Muscle mass analysis in women of different ages - Barbosa, Rhennan Rodrigues; Silva, Thiago Coelho de Aguiar; Lins, Tatiana Acioli; Almeida, Aline Pâmela dos Santos; Guimarães, Fernando José de Sá Pereira; Costa, Manoel da Cunha (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: During the aging process, significant changes in the pattern of distribution of morphological and structural variables such as body fat and muscle mass can be observed. Objective: To analyze the distribution of total and appendicular muscle mass in women in different age groups. Methods: The sample consisted of 129 women, aged between 50 and 80 years. The study was divided into two stages, composed of the anthropometric measures, total body mass (kg) and height (m) and body composition evaluation using DEXA. Results: There was a significant reduction in muscle mass with the advancement of age, and from age 60 and older, the age group showed a significant increase when compared to subjects of lower age, with a decrease of 1.65 kg in their total muscle mass. It should be noted that in our study, this progression increased in subjects older than 72 years, with a decrease of 2,10 kg in their total muscle mass. Conclusions: The reductions of muscle mass in the lower limbs presented greater amplitudes in comparison with the other regions of the analyzed human body, being an area with greater focus of analyzes with the objective of identifying and assisting the diagnosis of sarcopenia in future studies.